Solving the detour problem in navigation: a model of prefrontal and hippocampal interactions - Spiers, Hugo J.; Gilbert, Sam J. (Frontiers in Human Neuroscience, 2015)
Adapting behavior to accommodate changes in the environment is an important function of the nervous system. A universal problem for motile animals is the discovery that a learned route is blocked and detour is required. Given the substantial neuroscience research on spatial navigation and decision-making it is surprising that so little is known about how the brain solves the detour problem. Here we review the limited number of relevant functional neuroimaging, single unit recording and lesion studies. We find that while the prefrontal cortex consistently responds to detours, the hippocampus does not. Recent evidence suggests the hippocampus tracks information about the future path distance to the goal. Based on this evidence we postulate a conceptual model in which: Lateral prefrontal cortex provides a prediction error signal about the change in the path, frontopolar and superior prefrontal cortex support the re-formulation of the route plan as a novel subgoal and the hippocampus simulates the new path. More data will be required to validate this model and understand 1) how the system processes the different options and 2) deals with situations where a new path becomes available (i.e. shortcuts).